The Supply of Corporate Directors and Board Independence - Knyazeva, Anzhela; Knyazeva, Diana; Masulis, Ronald W. (Review of Financial Studies, 2013)
Empirical evidence on the relations between board independence and board decisions and firm performance is generally confounded by serious endogeneity issues. We circumvent these endogeneity problems by demonstrating the strong impact of the local director labor market on board composition. Specifically, we show that proximity to larger pools of local director talent leads to more independent boards for all but the largest quartile of S&P 1500. Using local director pools as an instrument for board independence, we document that board independence has a positive effect on firm value, operating performance, fraction of CEO incentive-based pay, and CEO turnover.